Optimizing Learning: Adaptive Technology Integration in Indonesia's Education System - Agustina, Rika Hasmayanti; Alfiyanto, Afif; Suhendri, Suhendri; Wihardjo, Edy; Pranajaya, Syatria Adymas (LPPM STKIP Kusuma Negara, 2025)
Adaptive technology in education offers an innovative solution to enhance learning quality by personalizing instructional materials according to students’ needs. This study aims to analyze the potential of adaptive technology in Indonesia’s education system and identify its implementation challenges. Using a literature review method, this research examines various studies on the application of adaptive technology in education, particularly within the